Co3O4–C3N4 p–n nano-heterojunctions for the simultaneous degradation of a mixture of pollutants under solar irradiation. Issue 1 (5th December 2016) - Suyana, P.; Ganguly, Priyanka; Nair, Balagopal N.; Mohamed, A. Peer; Warrier, K. G. K.; Hareesh, U. S.
Abstract : Sunlight active Co3 O4 –C3 N4 nano-heterojunctions for the effective removal of mixture of tetracycline antibiotic and methylene blue dye. Abstract : Environmental remediation employing sunlight-active semiconductor nano-heterostructures provides effective solutions for handling emerging contaminants through a greener approach. Herein, we report the creation of ultrafine dispersions of Co3 O4 nanoparticles in a g-C3 N4 matrix by a simple one-pot synthetic strategy involving the co-pyrolysis of constituent raw materials. Calcination of a homogeneous mixture of melamine and cobalt nitrate at 550 °C/2 h leads to the formation of Co3 O4 –C3 N4 p–n nano-heterojunctions that displayed extended absorption in the visible wavelength region owing to the synergistic role of Co3 O4 particles. Moreover, the surface area values of the composites reached 90 m 2 g −1, a tenfold increase from the value of 8 m 2 g −1 obtained for the pristine C3 N4 . The band bending, induced by the p–n nano-heterojunctions, leads to the formation of intimate interfaces having enhanced photophysical properties. The mass normalized photoluminescence spectra of the heterojunctions indicated reduced exciton recombinations that are validated further by the enhanced sunlight-induced photocatalytic degradation of a mixture of methylene blue and tetracycline organic pollutants.